(untitled) (Journal of Applied Learning and Teaching, 2022)
This interview follows up on a previous interview with Stephen Brookfield in the Journal of Applied Learning & Teaching (Brookfield et al., 2019). It was conducted as part of an ongoing book project with the working title Teaching well that the authors are involved in. This interview may be seen as a teaser for the book that is planned to be published in 2023. It constitutes an extended version of one out of 13 planned chapters and focuses on how power shows up in higher education classrooms. Classrooms are never power-free zones. Every learning environment contains student-to-student and student-to-teacher power dynamics. We discuss various influences on Stephen Brookfield’s conceptual understanding of power, especially Michel Foucault’s concepts of sovereign, disciplinary and bio-power and their applicability to education. In this context, we explore similarities between prisons and schools, the metaphor of the panopticon, and the continued relevance of bio-power during the current pandemic. The democratic practice of discussion groups is questioned (despite Stephen Brookfield’s personal preference of that modality) and the lecture is reinstated as one of several useful modalities. We then arrive at Brookfield’s concept of powerful teaching & learning and how teachers can exercise their power in ethical, productive and responsible ways. The interview ends with Brookfield’s advice on institutional criticism. Since beginning his teaching career in 1970, Stephen Brookfield has worked in England, Canada, Australia, and the U.S., teaching in a variety of adult, community, organisational and higher education settings (the latter include Harvard University and Columbia University). In his endeavour to help adults learn to think critically about the dominant ideologies they have internalised, Professor Brookfield has written, co-written or edited 20 books on adult learning and teaching, critical thinking, discussion methods, critical theory and teaching race.